Ibsen in the decolonised South Asian theatre - Huq, Sabiha; Mukherjee, Srideep (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book maps South Asian theatre productions that have contextualised Ibsen's plays to underscore the emergent challenges of postcolonial nation formation. The concerns addressed in this collection include politico-cultural engagements with human rights, economic and environmental issues, and globalization, all of which have evolved through colonial times and thereafter. This book contemplates why and how these Ibsen texts were repeatedly adapted for the stage, and consequently to reflect upon the political intent of this appropriative journey of the foreign playwright. This book tracks the unmapped agency that South Asian theatre has acquired through aesthetic appropriation of Ibsen, and thereby contributes to his global reception. This collection will be of great interest to students and scholars of theatre and performance studies"--
Post-colonial theatre and Ibsen productions in Pakistan : a historical overview / Asghar Nadeem Syed -- Intercultural assimilation of contraries in postcolonial South Asia : fluctuating movement of Ibsen's corpus / Kamaluddin Nilu -- Constructing a new identity space for women in post-colony : Sambhu Mitra's production of A Doll's House / Ahmed Ahsanuzzaman -- Women's movement in Pakistan : Tehrik-e-Niswan's A Doll's House in Urdu / Ishrat Lindblad -- Nora and the politics of gender in the postcolonial performance space in Sri Lanka / Kanchuka Dharmasiri & K Rathitharan -- Has the Indian 'doll' really evolved? : A Doll's House on decolonised Indian Stage(s) / Srideep Mukherjee -- Middle class liberal values and the Bangladeshi national imaginary : Ibsen's Ghosts Reconfigured / Manosh Chowdhury -- By means of Ibsen : theatre amidst rising fanaticism in post-partition India and Bangladesh / Sabiha Huq -- Kamaluddin Nilu's Three 'Peer's : Relocating Henrik Ibsen's Peer Gynt in South Asian contemporaneity / Imran Kamal -- Unheard voices & refracted essence : Bangla Adaptations of An Enemy of the People and The Pillars of Society / Tapati Gupta -- A Doll's House in Nepal : rationalising the appropriation of Putaliko Ghar / Menuka Gurung -- Peer Ghani and Peechha Karti Parchhaiyan : negotiating adaptation and appropriation / Astri Ghosh.
Includes bibliographical references and index.
ENH
Hye Trade International
Keywords: Ibsen, Henrik, -- 1828-1906 -- Dramatic production; Ibsen, Henrik, -- 1828-1906 -- Stage history -- South Asia; Ibsen, Henrik, -- 1828-1906 -- Appreciation -- South Asia; Theater and globalization -- South Asia